Konstens digitala upplevelserum : En upplevelseteoretisk fallstudie av två digitala besöksmål - Jonasson, Therese (2015)
This study is a Bachelor thesis in Experience Production at Luleå University of Technology - Department of Arts, Communication and Education. The purpose of the study is to examine what kind of experiences the two digital cases; Tate and MoMA, offer through their websites and also to test if the two experiencemodells can be used to analyze digital environments. The study aims to answer three research questions: • What type of generations experience is offered through Tate’s and MoMA’s websites? • What type of experiences is offered through Tate’s and MoMA’s websites based on the model The Experence Realms (Pine & Gilmore, 1999)? • Can the two selected experience theories be applied to theese two digital cases? To answer the three research questions I chose a deductive approach and a case study method theory. The two cases have been analyzed by two selected theories; The Experience Realms (Pine & Gilmore, 1999) and Actors in the creation of a meaningful experience (Boswijk et al., 2007). The results show that both cases offer all generations experiences accordning to Boswijk et al.s model (2007). Most of the digital sights, however, only offer conditions for first-generation experiences. The digital destinations also offer experience in all the experience fields in Pine & Gilmore's model (1999). Both models were very suitable to analyze digital experiences, which answers my third research question. I believe that the study can be seen as relevant to experience producers but also people working within the cultural and museum sector. Validerat; 20150609 (global_studentproject_submitter)